2019
DOI: 10.1371/journal.pone.0221731
|View full text |Cite
|
Sign up to set email alerts
|

Occult periprosthetic femoral fractures occur frequently during a long, trapezoidal, double-tapered cementless femoral stem fixation in primary THA

Abstract: The present study aimed to investigate the prevalence and clinical consequences of occult intra-operative periprosthetic femoral fractures in total hip arthroplasty (THA). Between 2012 and 2017, a total of 113 primary THAs were enrolled. The mean age of the patients was 66.4 ± 7.6 years. We assessed occult intra-operative periprosthetic femoral fractures with the use of computed tomography (CT) and risk factors, including age, sex, body mass index, diagnosis, stem size, and radiographic parameters of proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…Scans were carried out with a helical CT scanner (Lightspeed VCT; GE Medical Systems, Milwaukee, Wisconsin, USA) to quantify the contact state of the implant and femur and to detect post-operative occult fracture – a post-THA complication. 16,17 Scans were carried out using a slice thickness of 1 mm and a pitch of 2.5 mm. All preoperative planning and post-operative evaluations were completed using a CT-based templating software ZedHip (Lexi Co, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…Scans were carried out with a helical CT scanner (Lightspeed VCT; GE Medical Systems, Milwaukee, Wisconsin, USA) to quantify the contact state of the implant and femur and to detect post-operative occult fracture – a post-THA complication. 16,17 Scans were carried out using a slice thickness of 1 mm and a pitch of 2.5 mm. All preoperative planning and post-operative evaluations were completed using a CT-based templating software ZedHip (Lexi Co, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, biomechanical data show that addition of a stem collar decreases the incidence of periprosthetic fractures. 17–20 These data suggest that femoral press fit stems with simple proximal geometry and selection of collared stems are the surgeon-controlled variable that can decrease fracture risk. Stem design however must be coupled with a good surgical technique.…”
Section: Fracture Riskmentioning
confidence: 99%
“…26 Studies have also reported an increased rate of occult femoral IPPFx with double-tapered stems with a proximal and distal trapezoidal and quadrangular cross-section, respectively. 27 However, shorter cementless reduced femoral geometry stems have been shown to decrease fracture risk. 26 Femoral IPPFx can occur during both stem broaching and final component impaction.…”
Section: Implant Factorsmentioning
confidence: 99%
“…In this article, reference 42 is level II studies. References 2,3,4,5,6,7,8,9,10,11,13,15,16,18,19,20,21,22,26,27,28,33,41,43,45,47,48, and 49 are level III studies. References 14,23,30,34,44, and 46 are level IV studies.…”
Section: Referencesmentioning
confidence: 99%